Frontispiece: Cobalt Phenanthroline–Indole Macrocycles as Highly Active Electrocatalysts for Oxygen Reduction. Issue 44 (27th October 2014) - Quernheim, Martin; Liang, Haiwei; Su, Qi; Baumgarten, Martin; Koshino, Nobuyoshi; Higashimura, Hideyuki; Müllen, Klaus
<x xml:space="preserve">Abstract</x> Cobalt Electrocatalysts A series of novel mono‐ and binuclear Co‐N4 complexes, based on a new phenanthroline–indole macrocyclic ligand, were synthesized. It was demonstrated that these complexes support the direct four‐electron reduction of oxygen to water. Furthermore, electrochemical measurements revealed high electrocatalytic activities, methanol resistance, and a superior long‐term stability for the oxygen‐reduction reaction (ORR) under alkaline conditions. Thus, these structurally well‐defined non‐precious metal complexes represent an alternative to platinum‐based catalysts in fuel‐cell applications. For more details, see the Communication on page 14178 by K. Müllen and co‐workers.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>